2018
DOI: 10.3201/eid2402.171028
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication and Ebola-Specific Knowledge and Behavior during 2014–2015 Outbreak, Sierra Leone

Abstract: We assessed the effect of information sources on Ebola-specific knowledge and behavior during the 2014–2015 Ebola virus disease outbreak in Sierra Leone. We pooled data from 4 population-based knowledge, attitude, and practice surveys (August, October, and December 2014 and July 2015), with a total of 10,604 respondents. We created composite variables for exposures (information sources: electronic, print, new media, government, community) and outcomes (knowledge and misconceptions, protective and risk behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Community sources such as religious and traditional leaders were mentioned by only 10% of the sample, which is low compared with the Ebola outbreak when 60% heard messages through community leaders. 28 This can be explained by the timing of our survey; sensitisation and community engagement efforts were just starting. Community leaders remain trusted sources of information in Sierra Leone and should be mobilised for community engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Community sources such as religious and traditional leaders were mentioned by only 10% of the sample, which is low compared with the Ebola outbreak when 60% heard messages through community leaders. 28 This can be explained by the timing of our survey; sensitisation and community engagement efforts were just starting. Community leaders remain trusted sources of information in Sierra Leone and should be mobilised for community engagement.…”
Section: Discussionmentioning
confidence: 99%
“…When the virus spread to the capital, there was an exponential increase in cases for a few weeks in November 2014, before the outbreak was under control and the number of new patients started to go down until the last cases were managed in January 2016. The interview guide was informed by quantitative data analysis looking at the association between information sources and Ebola-specific knowledge and behaviour in Sierra Leone [30]. The study found associations between information channels like radio and knowledge, protective behaviour and misconceptions about the virus [30].…”
Section: Data Collectionmentioning
confidence: 99%
“…The interview guide was informed by quantitative data analysis looking at the association between information sources and Ebola-specific knowledge and behaviour in Sierra Leone [30]. The study found associations between information channels like radio and knowledge, protective behaviour and misconceptions about the virus [30]. The semi-structured interviews followed an interview guide, containing questions about journalists' awareness of Ebola before the outbreak, as well as questions about experiences, information sources, knowledge and behaviour during the outbreak.…”
Section: Data Collectionmentioning
confidence: 99%
“…Risk communication and social mobilization interventions aimed to inform and engage the public to elicit the desired behavioural change. Previous research in Sierra Leone found that exposure to information sources was associated with increased Ebola-specific knowledge and protective behaviours [15]. Risk perception is thought to be an important determinant of behaviour change [16,17].…”
Section: Introductionmentioning
confidence: 99%